Insight into maternal mortality of tertiary referral hospital of Madhya Pradesh: destination far ahead - Sahu, Bharti; Shukla, Padma; Khan, Shama; Sharma, Parwati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Demise of mother wreaks havoc in family, society and ultimately nation. Amongst so many countries, India alone contributes one quarter of total world maternal deaths. Millennium Development Goal targeted to cut down maternal mortality up to or less than 109 per lakh of total live births is far away from present level prevailing especially in our institution of Madhya Pradesh in centre of India. Methods: A retrospective analysis of maternal deaths from hospital records and death summaries of one year between Jan 2014 to Dec 2014 at NSCB Medical College and Hospital, Jabalpur in Madhya Pradesh. Results: During the review period, there were 75 maternal deaths and 5509 live births. (Institutional maternal mortality ratio, 1361.1 per lakh live births). All cases were analysed in detail: 70.6% (n = 53) were direct maternal deaths and PIH (n = 34, 45.33%) and Haemorrhage and sepsis (n = 7, 9.33%) were the leading causes of mortality. In indirect causes 29.33% (n = 22), severe anaemia topped (n=14, 18.66%). Women frequently did not attend prenatal clinics (n = 73, 97.33%),were resident of rural areas (n = 67, 89.33%) , referred (n = 68 , 90.66% ) most of them were of age of 20-30 years ( n=64, 82%) primigravida ( n = 45 , 60%),70% postnatal and experienced delays in care (n = 41 ,44.66%) and lost battle of life within 24 hrs. of admission. Conclusions: The burden of maternal mortality was found to be unacceptably high. Most women died of direct causes and experienced delays in care. Improvement in the quality of skilled maternity care, utmost need to avail good, proper and effective antenatal care, timely referral, prompt transportation, provision of family planning services, among other factors, can drastically curtail the maternal deaths.